SISTEM INFORMASI SUMBER DAYA MANUSIA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Rahayu, Sri; Selvi, Evi (Movere Journal, 2023)
Increasingly advanced developments require companies to update strategies within their companies, one of which is on strategies in human resources. Human resources owned by a good company will be seen from how the results of employee performance. And that many factors can affect employee performance, including human resource information systems and work motivation. This study aims to conclude from the problem of employee performance that occurs by collecting from various previous studies or by literature review. The variables in this study are Human Resource Information Systems, Work Motivation, and Employee Performance. The method in this study uses a literature study approach. The results of this study indicate that both the human resource information system and motivation can produce results that affect and do not affect employee performance due to the object of research, research time, and other factors that are not examined.